Risk and Consequences of Postoperative Delirium in Cardiac Surgery - Sugimura, Yukiharu; Sipahi, Nihat Firat; Mehdiani, Arash; Petrov, Georgi; Awe, Mareike; Minol, Jan Philipp; Boeken, Udo; Korbmacher, Bernhard; Lichtenberg, Artur; Dalyanoglu, Hannan (The Thoracic and Cardiovascular Surgeon, 2020)
Background Delirium is a common complication after cardiac surgery that leads to increased costs and worse outcomes. This retrospective study evaluated the potential risk factors and postoperative impact of delirium on cardiac surgery patients.Methods One thousand two hundred six patients who underwent open-heart surgery within a single year were included. Uni- and multivariate analyses of a variety of pre, intra-, and postoperative parameters were performed according to differences between the delirium (D) and nondelirium (ND) groups.Results The incidence of delirium was 11.6% (n = 140). The onset of delirium occurred at 3.35 ± 4.05 postoperative days with a duration of 5.97 ± 5.36 days. There were two important risk factors for postoperative delirium: higher age (D vs. ND, 73.1 ± 9.04 years vs. 69.0 ± 11.1 years, p < 0.001) and longer aortic cross-clamp time (D vs. ND, 69.8 ± 49.9 minutes vs. 61.6 ± 53.8 minutes, p < 0.05). We found that delirious patients developed significantly more frequent postoperative complications, such as myocardial infarction (MI) (D vs. ND, 1.43% [n = 3] vs. 0.28% [n = 2], p = 0.05), cerebrovascular accident (D vs. ND, 10.7% [n = 15] vs. 3.75% [n = 40], p < 0.001), respiratory complications (D vs. ND, 16.4% [n = 23] vs. 5.72% [n = 61], p < 0.001), and infections (D vs. ND, 36.4% [n = 51] vs. 16.0% [n = 170], p < 0.001). The hospital stay was longer in cases of postoperative delirium (D vs. ND, 23.2 ± 13.6 days vs. 17.4 ± 12.8 days, p < 0.001), and fewer patients were discharged home (D vs. ND, 56.0% [n = 65] vs. 66.8% [n = 571], p < 0.001).Conclusions Because the propensity for delirium-related complications is high after cardiac surgery, a practical, preventative strategy should be developed for patients with perioperative risk factors, including higher age and a longer cross-clamp time.
Keywords: cardiac surgery; complications; delirium; risk factors; outcome